Meeting the Challenge of COVID-19 Pandemic in Mental Health Care in a Tertiary-Care General Hospital in India - Sood, Mamta; Chadda, Rakesh K. (Annals of the National Academy of Medical Sciences (India), 2021)
Medical profession has proved its versatility in the adoption of many strategies to deal with the impact of COVID-19. All India Institute of Medical Sciences (AIIMS), New Delhi, India is a large public funded medical school and general hospital in North India. Psychiatry department is one of the 42 departments at AIIMS. COVID-19 has impacted all the functions of the department: clinical care, teaching and training, research and other roles. In this communication, we report the strategies, simple yet effective improvisations to meet the challenges of COVID-19 so as to continue the basic functions of the discipline. This could serve as a model for continued functioning of a tertiary care teaching medical facility in a pandemic situation.
Keywords: COVID-19; functioning; India; medical college; psychiatry